Value of research-based master's degree theses - Britt Sætre Hansen; Elin Dysvik (Cappelen Damm Akademisk NOASP, 2022)
Background: New types of expertise in advanced nursing is required to meet the rapid changes in health services and technologies. To meet these challenges, different master's degree programs are evolving, which will provide systematic introductions to analytical thinking and research-based argumentation and will lay the foundation for evidence-based nursing. Aim: The aim of this study was to investigate topics and methods in research-based master's degree theses in anesthesia, critical care, and operating room nursing (AIO) to explore their contribution to best practices within nursing specialization in anesthesia, intensive care, and operating theater nursing in Norway. Method: By using thematic analysis we examined 78 research-based master's degree theses produced over 5 years, representing the entire period of a university program in anesthesia, intensive care, and operating theater nursing. Findings: The master's theses covered different topics, ranging from topics within best practice, competence building and teamwork. A variety of methods were used to suggest improvements in the clinical field. This means that the value of the research topics chosen can be studied from different angles and help identify the complexity of the phenomena of interest. Conclusion: Master's degree thesis represents new, updated, and valuable knowledge for educational institutions, career development, hospital management, and clinical practitioners to guide future advanced and best practice both nationally and internationally.